Perilaku Pemilih Dalam Memanfaatkan Media Sosial Pada Pemilihan Bupati Dan Wakil Bupati Kabupaten Maros 2020 - Kamaruddin, Imran; Fatra, Emil (Jurnal Jurnalisa: Jurnal Jurusan Jurnalistik, 2023)
This research aims to provide very important information in the efforts of the KPU of Maros Regency as part of the Election Organizers to be able to increase the capacity and quality of holding general elections towards an ideal and democratic Pilkada in the future. This study also uses a quantitative approach, namely the researcher collects data by first establishing concepts as related variables originating from existing theories and then looking for data by using a questionnaire to measure these variables.Based on the results of data analysis and discussion, it can be concluded that: (1) The level of utilization of social media and digital media by candidate pairs is very high. The results showed that respondents' perceptions of candidate pairs utilizing digital media (websites, smartphone applications, online advertisements) in campaigns were very significant. There were 59 people or 59% who stated that digital media played a very important role as a promotional tool for candidate pairs. (2) The use of social media and digital media in the election of regents and deputy regents in Maros Regency in 2020 provides many advantages as political figure self-branding.